Impacts of COVID-19 on the Catch of Small-Scale Fishers and Their Families Due to Restriction Policies in Davao Gulf, Philippines - Macusi, Edison D.; Siblos, Stefenie Katrin V.; Betancourt, Martha Elena; Macusi, Erna S.; Calderon, Michael N.; Bersaldo, Michael Jeriel I.; Digal, Larry N. (Frontiers in Marine Science, 2022)
COVID-19 was declared a global pandemic by the World Health Organization in 2020 with countries putting up several measures to mitigate and flatten the curve of hospitalizations and death from travel bans to home confinements and local lockdowns. This pandemic created health and economic crises, leading to increased incidence of poverty and food crisis especially on both agriculture and the fisheries in many developing nations including the Philippines. The specific objectives of this study were to assess the impact of COVID-19 restrictions on the catch per unit effort (CPUE) of small-scale fishers and to determine what factors could influence the volume of their catch during this time of pandemic. Moreover, this also investigated the impact of COVID-19 restrictions to fishers and their families. To do that we surveyed N = 200 small-scale fishers around the Davao gulf using semi-structured questionnaire and inquired on the impact of the COVID-19 to their fishing operation, catch, fishing costs, and their families. The collected socioeconomic variables, including emotional responses to the pandemic were then related to the CPUE and the volume of catch. The results show that fishers were highly affected by the pandemic due to the lockdown policy imposed in the fishing villages during the earlier phases of restrictions by the government. Fishers were affected in terms of the volume of their catch, also fishing costs, and emotionally as they were also frustrated due to the impacts of the hard lockdown. The restricted fishing access was found to have important and major set-back on the fishing operations of fishers and the same was experienced also by the middlemen given the low fish price and reduced mobility of the fish traders. COVID-19 also impacted the fishers, and their families through lack of mobility, food inadequacy, travel restrictions and their children’s education.